2008
DOI: 10.1021/es8003969
|View full text |Cite
|
Sign up to set email alerts
|

Affinity of Microbial Fuel Cell Biofilm for the Anodic Potential

Abstract: In analogy to the well established dependency of microbial reactions on the redox potential of the terminal electron acceptor, the dependency of the microbial activity in a highly active microbial fuel cell on the potential of the electron-accepting electrode (anode) in a microbial fuel cell (MFC) is investigated. An acetate-fed, pH-controlled MFC was operated for over 200 days to establish a highly active MFC anodic biofilm using ferricyanide as the catholyte and granular graphite as electrode material. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 20 publications
4
59
1
Order By: Relevance
“…Experimental runs were performed in a two-chamber bioelectrochemical cell made of transparent Perspex as described in (Cheng et al, 2008). The two chambers were physically separated by a cation exchange membrane (CMI-7000, Membrane International Inc.) with a surface area of 168 cm 2 and were identical in volume and dimension (350 mL (14 cm x 12.5 cm x 2 cm)).…”
Section: Bioelectrochemical Cell Construction and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental runs were performed in a two-chamber bioelectrochemical cell made of transparent Perspex as described in (Cheng et al, 2008). The two chambers were physically separated by a cation exchange membrane (CMI-7000, Membrane International Inc.) with a surface area of 168 cm 2 and were identical in volume and dimension (350 mL (14 cm x 12.5 cm x 2 cm)).…”
Section: Bioelectrochemical Cell Construction and Monitoringmentioning
confidence: 99%
“…2.0 g L -1 . It was mixed with a synthetic wastewater (10 %, v/v) as described in Cheng et al (2008). Initially, 50 mM potassium ferricyanide K 3 Fe(CN) 6 (Sigma-Aldrich, Inc., Purity ca.…”
Section: Process Startup and Operationmentioning
confidence: 99%
“…So, the proposition can be proved if it can be shown that Moving S f (S f +S 0 )/2(K S,m + 2S f ) to the right-hand side, removing the denominators, and rearranging gives Equation 24 can be further simplified to …”
Section: Optimization Of Substratementioning
confidence: 99%
“…For maximum power production, the anodic potential of a MFC is negative and the cathode potential positive (Cheng et al, 2008). In this study, the MFC is not used for obtaining electricity output but to be used as a biosensor to detect low levels of AOC by using a potentiostat which typically keeps the cathode more negative than the anode.…”
Section: Operation Of the Marine Mfc Biosensor Without Oxygen Removalmentioning
confidence: 99%
“…AOC is one of the main food sources for bacteria to proliferate and hence it is more appropriate to be used as an indicator of the relative biofouling potential of feed-water (Jeong et al, 2013). Other attempts at AOC tests such as biochemical oxygen demand BOD 5 (Bourgeois et al A typical MFC-biosensor consists of an anodic chamber (anaerobic) and a cathodic chamber separated by a cation exchange membrane. The active anodophilic bacteria oxidise organic carbon in the anodic chamber and generate electrons and protons.…”
Section: Introductionmentioning
confidence: 99%